Start late, finish rich : a no-fail plan for achieving financial freedom at any age - Bach, David, 4 0 16; 5 (New York : Broadway Books, 2006)
Presents a comprehensive guide to building a secure financial future and shows how to spend less and save more, begin a business, or make money in real estate by starting small.
Includes index.
Library Journal, January 2005;Booklist, December 2004;Library Journal;Booklist
Adult;Adult
Keywords: 2 -- 0; 6; Finance, Personal.;Investments.;Financial security.;Personal finance.;Investments.; 20; 2